Pengaruh Lingkungan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan Kopi nJongke dengan Organizational Citizenship Behavior (OCB) sebagai Pemediasi - Novia Valentin Dua Subu; Nur Rokhman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
Many factors can affect employee performance, such as work environment, organizational commitment and organizational citizenship behavior. The purpose of this study was to analyze the effect of the work environment on employee performance, the effect of organizational commitment on employee performance, the effect of the work environment on organizational citizenship behavior, the effect of organizational commitment on organizational citizenship behavior, the effect of organizational citizenship behavior on employee performance, the indirect effect of work environment on performance employees through organizational citizenship behavior, and the indirect effect of organizational commitment on employee performance through organizational citizenship behavior. The sampling technique uses the saturated sample method. The number of samples used were 34 respondents. The data collection technique uses a questionnaire that is distributed using the Google form. The analysis technique used in this study is path analysis, which was processed using SPSS version 26. The results showed that all hypotheses were proven, both hypothesis 1 to hypothesis 7 were proven. All variables both work environment, organizational commitment, work environment have a positive and significant effect on organizational citizenship behavior. Meanwhile organizational commitment has a positive and significant effect on organizational citizenship behavior, organizational citizenship behavior has a positive and significant effect on employee performance, organizational citizenship behavior has been shown to mediate the relationship between work environment and employee performance, and organizational citizenship behavior mediates the relationship between organizational commitment and employee performance.